Peran Auditor Internal Pemerintah dalam Pencegahan dan Pendeteksian Fraud (Sebuah Studi Fenomenologi) - Darori, Darori (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This study aims to explore the meaning and problems of the role of internal government auditors in the prevention and detection of fraud. This research uses transcendental phenomenology approach through the stages of analysis: Description of phenomena; Identify the themes; Linking noesis and noema as well as the last abstract or universal stage of noetic / noematic corelations. Data collection is done through interviews, observations, and documentation. The research finds the role of government internal auditors as bodyguards of the organization to stay on the track. The role of the current internal auditor is not just a watchdog but a consultant. The role of auditor can not be done well because continuity prevention program does not run, Testing of internal control system still limited formalities, competence auditor uneven and performance audit not optimal.